VARIATION OF SOLVENT COMPOSITION EFFECT ON PERFORMANCE AND PHYSICOCHEMICAL PROPERTIES OF CELLULOSE ACETATE MEMBRANE - Dwi Indarti; Nanda Widayanti; Neran Neran (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2012)
Performance Cellulose acetate (CA) were characterized by the variation of solvent composition (acetone and formic acid) with a mole ratio of 5/10; 6/9; 7/8; 8.7; and 9/6 and the addition of additives MSG 6%. Characterization was conducted on the membrane performance (flux, permeability coefficient,% rejection) and physicochemical properties include density test and analysis of membrane structure by FTIR. Membrane solvent variation results, 6/9 has the lowest density values. Results flux, permeability coefficient and the highest rejection is obtained when the composition of the 9/6. FTIR test results showed no difference between the polymer cellulose acetate cellulose acetate membrane solvent variation results.